Menelusuri Jejak Ijtihad: Metode Dewan Hisbah Persatuan Islam dalam Merespons Isu Zaman - Titing Oting Supartini; Ending Solehudin (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2025)
This study discusses the ijtihad method used by the Hisbah Council of Islamic Unity (PERSIS), one of the major Islamic organizations in Indonesia known for its commitment to the purification (tajdīd) of Islamic teachings. This research is motivated by the importance of understanding how religious institutions respond to socio-religious dynamics through a distinctive ijtihad mechanism. The main purpose of this study is to analyze the methodological approach of the Hisbah Council in formulating fatwas of contemporary Islamic law. This research uses a qualitative approach with a descriptive-analytical method. Data collection was carried out through a literature study of the official fatwa documents of the Hisbah Council, minutes of deliberations, and supporting literature related to the methodology of ijtihad and Persis Islamic thought. The results of the study show that the ijtihad method of the Hisbah Council is textualist-scriptural with an emphasis on the postulates of the Qur'an, sahih hadith, and qiyās. They reject the blind form of taklid as well as the use of istihsān and maṣlaḥah mursalah methods which are considered loose or do not have a strong nash basis. This study shows that the Hisbah Council maintains epistemological consistency in maintaining the purity of Islamic legal sources, but still shows a selective attitude in responding to contemporary issues. This strengthens the position of the Hisbah Council as an influential ijtihad authority in shaping the direction of religious thought of the Islamic Union in the modern era.